Privacy-preserving multi-attribute reverse spectrum auction scheme - Jiaqi WANG; Ning LU; Qingfeng CHENG; Zhaoxia WU; Wenbo SHI (Tongxin xuebao)
Aiming the problem that the existing reverse spectrum auctions do not take the non-price attribute of spectrum into account and the security of spectrum auction,a privacy-preserving multi-attribute reverse spectrum auction was proposed.Firstly,price and non-price positive attributes of spectrum were considered as the bidding scheme of bidders and auctions was performed to judge spectrum winners.Secondly,to ensure the security of the spectrum auction,the Paillier threshold system was used to introduce a group of spectrum auction servers of auctioneers to replace the traditional single third-party agency,which could prevent the fraud collusion between spectrum auctioneers and bidders.The cryptography tools such as the anonymization technology and oblivious transfer were introduced to achieve the secure features,which could make the spectrum auction performed securely.The security analysis shows that the security protocol has strong security.The performance of the protocol is also evaluated,and experimental results show that the security scheme is superior to the multi-attribute reverse auction security scheme that can be applied in the spectrum auction scenario in terms of computational overhead.